Está en la página 1de 1

P

P L P 2 P 2 PL 8 P PL 8 PL 8 P P 2
P L P 2 P 2 PL 8 P PL 8 PL 8 P P 2

L

P L P 2 P 2 PL 8 P PL 8 PL 8 P P 2

P

2

P L P 2 P 2 PL 8 P PL 8 PL 8 P P 2

P

2

P L P 2 P 2 PL 8 P PL 8 PL 8 P P 2

PL

8

P L P 2 P 2 PL 8 P PL 8 PL 8 P P 2

P

PL

8

PL

8

P L P 2 P 2 PL 8 P PL 8 PL 8 P P 2
P P

P

P

P P

2

PL

8
8
2
2
P L P 2 P 2 PL 8 P PL 8 PL 8 P P 2
P L P 2 P 2 PL 8 P PL 8 PL 8 P P 2

PL

8

q

q

L
L

qL 2

12

q q L qL 2 12 qL qL 2 2 qL 2 qL 2 12 24
q q L qL 2 12 qL qL 2 2 qL 2 qL 2 12 24

qL

qL

2

2

qL 2

q q L qL 2 12 qL qL 2 2 qL 2 qL 2 12 24

qL 2

12

q q L qL 2 12 qL qL 2 2 qL 2 qL 2 12 24
24 qL 2 qL 2 12 12 q qL qL 2 2 qL 2 qL
24
qL 2
qL 2
12
12
q
qL
qL
2
2
qL
2
qL
2

qL

2

qL

2

q

L
L
q L T i L T s > T i F T > 0 ε T
T i
T i

L

T s > T i

F T

> 0

ε T = α ( T s + T i )

2

F T = ε T A E

T
T
( T s + T i ) 2 ⇒ F T = ε T A E
( T s + T i ) 2 ⇒ F T = ε T A E

T i

M T

F T

T i ) 2 ⇒ F T = ε T A E T T i M

F T

i ) 2 ⇒ F T = ε T A E T T i M T

L

) 2 ⇒ F T = ε T A E T T i M T F
) 2 ⇒ F T = ε T A E T T i M T F
) 2 ⇒ F T = ε T A E T T i M T F
) 2 ⇒ F T = ε T A E T T i M T F
) 2 ⇒ F T = ε T A E T T i M T F

L + e

 
 
 

F

e

 
  F e

F

e

F e = e A E

L

F e

T s

M

T s

κ T = α ( T s T i )

h

M T = κ T E I

κ T = α ( T s − T i ) h ⇒ M T =
κ T = α ( T s − T i ) h ⇒ M T =

M T